2009
DOI: 10.1007/s11689-009-9029-4
|View full text |Cite
|
Sign up to set email alerts
|

Verbal short-term memory deficits in Down syndrome: phonological, semantic, or both?

Abstract: The current study examined the phonological and semantic contributions to the verbal short-term memory (VSTM) deficit in Down syndrome (DS) by experimentally manipulating the phonological and semantic demands of VSTM tasks. The performance of 18 individuals with DS (ages 11–25) and 18 typically developing children (ages 3–10) matched pairwise on receptive vocabulary and gender was compared on four VSTM tasks, two tapping phonological VSTM (phonological similarity, nonword discrimination) and two tapping semant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 59 publications
0
11
0
1
Order By: Relevance
“…Delayed recall, or long-term memory, in individuals with DS also has been described as variable, with a dissociation being reported for implicit and explicit types of long-term memory, in favor of the former (Carlesimo, Marotta, & Vicari, 1997). Consequently, a targeted clinical trial assessment strategy for memory appears to point to short- and long-term explicit memory functions across both verbal and nonverbal domains (Lee, Pennington, & Keenan, 2010). …”
Section: Resultsmentioning
confidence: 99%
“…Delayed recall, or long-term memory, in individuals with DS also has been described as variable, with a dissociation being reported for implicit and explicit types of long-term memory, in favor of the former (Carlesimo, Marotta, & Vicari, 1997). Consequently, a targeted clinical trial assessment strategy for memory appears to point to short- and long-term explicit memory functions across both verbal and nonverbal domains (Lee, Pennington, & Keenan, 2010). …”
Section: Resultsmentioning
confidence: 99%
“…Five of these studies compared groups with DS and TD. Two reported no significant difference between groups, with one study matching on general MA (Vicari et al, 2004) and the other matching on receptive vocabulary (Lee, Pennington, & Keenan, 2010). Two found the group with DS performed more poorly than the TD group when matched on general MA (Bihrle, 1990) or receptive vocabulary (Cornish et al, 1999).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the extant literature suggests that individuals with DS perform more poorly on working memory tasks with an auditory component and that this impairment is related to language processing (see Conners 2003 for a review), particularly in the phonological domain (Lee, Pennington, & Keenan, 2010). Over 60% of the DS study group showed clinical levels of impairment in this area by both teachers and parents, when compared to a MA- matched comparison group.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, when examining the magnitude of this working memory deficit utilizing Cohen’s d (Cohen, 1988), a measure of effect size, we find Cohen’s d to be 1.8 for teachers and 1.4 for parents. As a direct comparison to the lab-based working/short-term memory literature focused on the verbal domain, we refer to Lee et al (2010) who calculated the mean effect size (and 95% CI) of this impairment for eight published studies that compared DS performance to that of mental-aged matched TD controls. They reported a mean effect size of 1.97 with a 95% confidence interval of 1.18 to 2.75.…”
Section: Discussionmentioning
confidence: 99%